2015
DOI: 10.1302/0301-620x.97b2.34554
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the incidence of early periprosthetic infection with silver-treated endoprostheses in high-risk patients

Abstract: We conducted a case-control study to examine the merit of silver-coated tumour prostheses. We reviewed 85 patients with Agluna-treated (silver-coated) tumour implants treated between 2006 and 2011 and matched them with 85 control patients treated between 2001 and 2011 with identical, but uncoated, tumour prostheses. In all, 106 men and 64 women with a mean age of 42.2 years (18.4 to 90.4) were included in the study. There were 50 primary reconstructions (29.4%); 79 one-stage revisions (46.5%) and 41 two-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 29 publications
7
138
1
3
Order By: Relevance
“…Similar to their group, given the morbidity of infection in these implants, it is now our practice to place all patients with prostheses that extend into the diaphysis on empiric chronic antibiotic therapy postoperatively. Investigation of this prolonged antibiotic course as well as collaborative efforts with oncology colleagues on interventions like local antibiotic delivery or silver-coated prostheses warrants future attention [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to their group, given the morbidity of infection in these implants, it is now our practice to place all patients with prostheses that extend into the diaphysis on empiric chronic antibiotic therapy postoperatively. Investigation of this prolonged antibiotic course as well as collaborative efforts with oncology colleagues on interventions like local antibiotic delivery or silver-coated prostheses warrants future attention [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical studies have shown promising results with regard to reducing periprosthetic infections. Wafa et al [49] retrospectively compared 85 patients with silvercoated tumor prostheses to 85 tumor patients with non-silver tumor prostheses. The authors found that the average infection rate among silver-coated implant patients was 10.6% lower than that of their uncoated counterparts.…”
Section: Nano-silver Coatingsmentioning
confidence: 99%
“…Aunque la plata posiblemente muestre menor actividad al ligarse a otras proteínas, mantiene la esterilidad de la superficie del implante ante la colonización bacteriana proveniente de las partes blandas (10) . Algunos autores han obtenido resultados que corroboran una menor tasa de infección con prótesis tumorales con recubrimiento de plata tras compararlas con otro grupo de pacientes en que se implantaron prótesis sin dicho recubrimiento, mostrando menores tasas de infección precoz y crónica (21) . Tras los resultados obtenidos en pacientes oncológicos, nuevas líneas de investigación se están abriendo, como el uso de recubrimientos de hidroxiapatita-plata para prótesis, que han demostrado la capacidad para inhibir el crecimiento bacteriano en estudios in vitro (22) .…”
Section: Discussionunclassified